Strategi Pemasaran Digital Pada UMKM Bakso Haji Lili Karawang - Benaya Mikhael Wijaya; Uus Mohammad Darul Fadli (Global Leadership Organizational Research in Management, 2024)
This research is motivated by the importance of digitization in marketing strategies to enhance the competitiveness of SMEs. Bakso Haji Lili Karawang, an SME adopting digital marketing, is the subject of this study. The aim of the research is to identify the effectiveness of digital marketing strategies implemented in increasing sales and brand awareness. The research methodology uses a quantitative approach by distributing questionnaires to consumers of Bakso Haji Lili Karawang and analyzing the data using descriptive statistics and linear regression. The results show that the use of social media, online advertising, and digital content significantly contributes to the increase in sales and brand awareness of Bakso Haji Lili Karawang. These findings provide insights for other SMEs on the importance of integrating digital marketing strategies into their business operations.